CHANGE DETECTION OF CROPPING PATTERN IN PADDY FIELD USING MULTI SPECTRAL SATELLITE DATA FOR ESTIMATING IRRIGATION WATER NEEDED - Shofiyati, Rizatus; Uchida, Satoshi; Sarwani, Muhrizal; H. Ismullah, Ishak (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
This paper investigates the use of multi spectral satellite data for cropping pattern monitoring in paddy field. The southern coastal of Citarum watershed, West Java Province was selected as study sites. The analysis used in this study is identifying crop pattern based on growth stages of wetland paddy and other crops by investigating the characteristic of Normalized Difference Vegetation Indices (NDVI) and Wetness of Tasseled Cap Transformation (TCT) derived from 14 scenes of Landsat TM date 1988 to 2001. In general, the phenological of growth stages of wetland paddy can be used to distinguish with other seasonal crops. The research results indicate that multi spectral satellite data has a great potential for identification and monitoring cropping pattern in paddy field. Specific character of NDVI and Wetness also can produce a map of cropping pattern in paddy field that is useful to monitor agricultural land condition. The cropping pattern can also be used to estimate irrigation water needed of paddy field in the area. Expected implication of the information obtained from this analysis is useful for guidance more appropriate planning and better management of agricultural.